2017
DOI: 10.1371/journal.pone.0177555
|View full text |Cite
|
Sign up to set email alerts
|

Is survival improved by the use of NIV and PEG in amyotrophic lateral sclerosis (ALS)? A post-mortem study of 80 ALS patients

Abstract: BackgroundNon-invasive ventilation (NIV) and percutaneous gastrostomy (PEG) are guideline-recommended interventions for symptom management in amyotrophic lateral sclerosis (ALS). Their effect on survival is controversial and the impact on causes of death is unknown.ObjectiveTo investigate the effect of NIV and PEG on survival and causes of death in ALS patients.MethodsEighty deceased ALS patients underwent a complete post mortem analysis for causes of death between 2003 and 2015. Forty-two of these patients co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
75
1
21

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(103 citation statements)
references
References 34 publications
3
75
1
21
Order By: Relevance
“…While no relationship was found with mood, there was a very strong association with PEG nutritional supplements and increased survival duration in the Chi-square test and the conditional random forests (Figure 4) conducted in the present study. The significance of PEG usage in associatively increasing survival is corroborated by recent work [20,53].…”
Section: Palliative Als Interventions Associated With Improved Mood Amentioning
confidence: 61%
“…While no relationship was found with mood, there was a very strong association with PEG nutritional supplements and increased survival duration in the Chi-square test and the conditional random forests (Figure 4) conducted in the present study. The significance of PEG usage in associatively increasing survival is corroborated by recent work [20,53].…”
Section: Palliative Als Interventions Associated With Improved Mood Amentioning
confidence: 61%
“…Our previous study using a Kaplan-Meier analysis did not find NIPPV to affect survival time, albeit an adjusted Cox proportional hazard model showed NIPPV to have a positive effect on the survival rate ( 35 ). Similarly, another study identified NIPPV as a significant survival-promoting factor with Cox proportional hazard regression after adjusting for various cofactors ( 36 ). A study in Taiwan using multivariate logistic regression also identified NIPPV as a predictor of long-term survival ( 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…Second, other factors may also be involved in disease progression, such as cognitive status, neuropsychological features, and pulmonary function, none of which was investigated at the time of this study. Third, even though an association between genetic variants and different clinical ALS profiles has been identified in several studies ( 1 , 36 ), we did not explore the influence of genetic variants on the staging system.…”
Section: Discussionmentioning
confidence: 99%
“…PEG has been associated with increased survival in people with ALS. 33,34 It is also associated with improved quality of life in~85% of patients who receive it, with no patients reporting worsened quality of life. 9 Clinical guidelines recommend early tube placement so that patients can benefit from nutritional support before malnutrition, weight loss, and dehydration have further progressed, and before patients are no longer candidates for the surgery to implant a PEG tube.…”
Section: Discussionmentioning
confidence: 99%